SFCL-SMES Control for Power System Transient Stability Enhancement Including SCIG-based Wind Generators - Zebar, A.; Madani, L. (Engineering, Technology & Applied Science Research, 2020)
The resolution of the environment pollution depends on renewable energy sources, such as wind energy systems. These systems face transient and voltage stability issues with wind energy employing fixed-speed induction generators to be augmented with resistive type Superconducting Fault Current Limiter (SFCL) and Superconducting Magnetic Energy Storage (SMES) devices. The use of a combined model based on SFCL and SMES for promoting transient and voltage stability of a multi-machine power system considering the fixed-speed induction generators is the primary focus of this study. Our contribution is the development of a new model that combines the advantages of SFCL and SMES. The proposed model functions assure flexible control of reactive power using SMES controller while reducing fault current using superconducting technology-based SFCL. The effectiveness of the proposed combined model is tested on the IEEE11-bus test system applied to the case of a three-phase short circuit fault in one transmission line.